Effect of the Use of E-Module Media on Student Learning Interest in Islamic Education Subjects - Faathrias Permata Niar; Nurul Latifatul Inayati (JIE (Journal of Islamic Education), 2024)
This study aimed to identify the effect of e-module utilization on students' interest in learning Islamic education subjects at Muhammadiyah Al-Kautsar Junior High School Special Program Kartasura. This research analyzes data in the form of numbers, known as quantitative research. Data were collected through interviews, observations, documentation, and the distribution of research questionnaires. From 95 populations, researchers took a sample of 30 students of grade VIII of Muhammadiyah Al-Kautsar Junior High School, teachers teaching Tarikh Education subjects, and coordinators of digital school programs. The collected data were then calculated using SPSS with a simple linear regression analysis test. The aim is to identify the effect of the independent variable (e-module utilization) on the dependent variable (student interest in learning). The basis for the simple linear regression test decision is to compare the significance value (sig.) with a probability value of 0.05. The results of the data calculation show that the sig. 0,000 < 0,05. The use of e-modules influences students' interest in learning. The magnitude of the influence between the use of e-modules on students' interest in learning is 40.4%.